1966
DOI: 10.2466/pr0.1966.18.3.803
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Deprivation and Sensory Reinforcement with Shock

Abstract: Groups of rats were raised from weaning under normal animal colony conditions and conditions of reduced sensory stimulation. In a shuttle box groups of 5, 2, and 2 showed acquisition for mild shock proportional to degree of deprivation ( P < .02). In a second experiment 16 deprived animals preferred shock more than did 14 nondeprived animals ( P < .01). Nondeprived rats preferred shock to no shock ( P < .01). The results are interpreted as effects of arousal and satiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Harrington & Linder (1962) proposed the use of mild shock as the most appropriate test of this hypothesis and reported reinforcing effects when shock was substituted for another sensory reinforcement. Subsequently it was shown that rats would acquire a shuttle box response for mild shock positive reinforcement (Harrington & Kohler, 1966). The present study extends these investigations to operant acquisition in a shock contingent bar press situation.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Harrington & Linder (1962) proposed the use of mild shock as the most appropriate test of this hypothesis and reported reinforcing effects when shock was substituted for another sensory reinforcement. Subsequently it was shown that rats would acquire a shuttle box response for mild shock positive reinforcement (Harrington & Kohler, 1966). The present study extends these investigations to operant acquisition in a shock contingent bar press situation.…”
supporting
confidence: 68%
“…Premack & Collier (1962) observed that short-term pretest adaptation to test apparatus enhanced light contingent bar press and remarked that this was the least understood of their outcomes. It has been suggested (Harrington, 1963;Harrington & Kohler, 1966) that sensorY reinforcement can be interpreted in terms of simultaneous action of arousal and satiation variables. This is interpreted to mean that with adaptation there is satiation on the stimuli present during adaptation.…”
mentioning
confidence: 99%
“…Melzack, 1962), patterns of exploratory activity (e.g. Zimbardo & Montgomery, 1957), or reactivity to shock (Harrington & Kohler, 1966;Lore, 1969) could contribute to differences in performance on the task, groups of blind and sighted, LR and D R rats were tested under appetitive and aversive motivation. If such variables d o have a significant impact, comparison of the maze performance of the various groups of animals under the 2 conditions of rearing should reveal it.…”
Section: Tees Midgley and Nesbitmentioning
confidence: 99%
“…Admittedly, there may be practical examples in which seemingly “bad” things appear to have become “good.” For example, Harrington and Kohler (1966) found that between animals reared in deprivation versus those reared in normal environments, those in deprived environments demonstrated a preference for shock. More recently, Wilson and colleagues (2014) tested the effect of stimulation deprivation on college students.…”
Section: Motivating-operation Effects On Reinforcement and Punishment...mentioning
confidence: 99%